The Development of Creative Dance Based Anti Bullying Educational Media to Foster Children's Empathic Imagination in the Laboratory Kindergarten of Universitas Negeri Malang - Winda Istiandini; Wida Rahayuningtyas; Ari Wibowo Kurniawan (Universitas Negeri Semarang, 2025)
The phenomenon of bullying in early childhood, especially among Generation Alpha who have minimal direct interaction, requires creative and interactive educational media to develop empathy. Although dance has proven to be effective in social development, the specific implementation of creative dance as an anti-bullying medium in Indonesia is still very limited. This study aims to develop and test the feasibility (validity and practicality) of creative dance-based anti-bullying educational media to foster empathic imagination in children in KB-TK Lab UM. This research uses a Research and Development (R&D) approach by adopting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The product developed is in the form of a creative dance video with the song